Effect of topology of poly(L-lactide-co-ε-caprolactone) scaffolds on the response of cultured human umbilical cord Whartons jelly-derived mesenchymal stem cells and neuroblastoma cell lines - Boontharika Thapsukhon (2018)
In this study, for the first time, a biodegradable poly(L-lactide-co- ε-caprolactone), PLC 67:33 copolymer was developed for use as temporary scaffolds in reconstructive nerve surgery. The effect of the surface topology and pore architecture were studied on the biocompatibility for supporting the growth of human umbilical cord Whartons jelly-derived mesenchymal stem cells (hWJ-MSCs) and human neuroblastoma cells (hNBCs) as cell models. Porous PLC membranes were prepared by electrospinning and phase immersion precipitation with particulate leaching and nonporous PLC membranes were prepared by solvent casting. From the results, the porous PLC membranes can support hWJ-MSCs and hNBCs cells better than the nonporous PLC membrane, and the interconnected pore scaffold prepared by electrospinning exhibited a more significant supporting attachment of the cells than the open pore and nonporous membranes. We can consider that these electrospun PLC membranes with 3-D interconnecting fiber networks and a high porosity warrant a potential use as nerve guides in reconstructive nerve surgery. © 2014 Taylor & Francis.